Investigation of the effect of “Orange Peel” surface texture on the laser sintered part - Wan Yusoff, Wan Ahmad Yusmawiza; A. Nasir, Safwa; Ahmad, Wan Mohamad Hakimi (IEEE, 2011)
The purpose of this research is to investigate the effect of “Orange Peel” surface texture into the part’s surface finish. The research analyzes the surface and microstructure of the “Orange Peel” surface texture of the laser sintered parts. The “Orange Peel” surface was identified to undergo surface roughness measurement and microstructure analysis. Then, a classification of the degree of “Orange Peel” severity was proposed based on the surface roughness measurement result. Finally, it was found that parts from recycle powder has poorer surface texture and has a large portion of unsintered powder particles. Based on the findings, a better understanding on powder recycling is defined especially in the scope of surface roughness and microstructure. The result will allow researcher to make improvement in laser sintering process.